Neurosurgical and Perioperative Management of Chronic Subdural Hematoma - Blaauw, Jurre; Jacobs, Bram; den Hertog, Heleen M.; van der Gaag, Niels A.; Jellema, Korné; Dammers, Ruben; Lingsma, Hester F.; Naalt, Joukje van der; Kho, Kuan H.; Groen, Rob J. M. (Frontiers in Neurology, 2020)
Objective Surgery and specifically burr hole craniostomy is the most common first choice treatment of patients with Chronic Subdural Hematoma (CSDH). However, several aspects of neurosurgical and peri-operative management are still a subject of research, such as how to treat bilateral CSDH and the anesthetic approach. We aim to investigate the effect of the surgical approach to bilateral CSDH and the effect of anesthesia modality on outcome of CSDH patients. Methods: We retrospectively included surgically treated CSDH patients between 2005 and 2019 in three hospitals in the Netherlands. The effect of the surgical approach to bilateral CSDH (unilateral vs. bilateral decompression) and anesthesia modality (general vs. local anesthesia) on outcome (complications, recurrence and length of hospital stay over 4 days) was studied with logistic regression adjusting for potentially confounding radiological and clinical characteristics. Results Data of 1029 consecutive patients were analyzed, mean age was 73.5 years (± 11) and 75% of patients were male. Bilateral CSDH is independently associated with an increased risk of recurrence within 3 months in logistic regression analysis (aOR 1.7, 95% CI: 1.1 – 2.5) but recurrence rate did not differ between primary bilateral or unilateral decompression of bilateral CSDH. (15% vs. 17%, p=0.775). Logistic regression analysis showed that general anesthesia was independently associated with an increased risk of complications (aOR 1.8, 95% CI: 1.0 – 3.3) and with a length of hospital admission of over 4 days (aOR 8.4, 95% CI: 5.6 – 12.4). Conclusions Bilateral CSDH is independently associated with higher recurrence rates. As recurrence rates in bilateral CSDH are similar for different surgical approaches, the optimal choice for primary bilateral decompression of bilateral CSDH could vary per patient. General anesthesia for surgical treatment of CSDH is associated with higher complication rates and longer hospital admission.